Genesis 24:48–54 and the role of mediator(s) in the marriage practice in Awkunanaw, Enugu State, Nigeria - Ugwuewo, Chisom S.; Ugwu, Amarachi S. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2025)
A middle person plays an important role in marriage practice especially in Igboland. This study remains significant in shaping cultural customs in Awkunanaw. This study aimed to analyse Genesis 24:48–54 within its original context and apply its exegetical insights to the cultural realities of Awkunanaw. The research design adopted is exegetical, using a narrative method of biblical exegesis to study the text. Data were collected and analysed qualitatively. The findings reveal that, in contemporary Igboland in general and Awkunanaw in particular, some middle persons have abused the trust placed in them, using their positions for selfish ends. In Genesis 24:48–54, Eliezer, the intermediary between Abraham’s family and Bethuel’s family in the marriage arrangement of Isaac and Rebekah, remained committed and faithful to his mission. The opposite, however, is often the case today. Many modern intermediaries in Awkunanaw exploit their positions for various ulterior motives. The findings indicated that such abuse of mediatory roles in marriage practices has jeopardised the cherished cultural heritage of the people. The current tendency to neglect the mediatory roles of adults and experienced elders in marital relations is a serious concern that needs urgent attention to ensure better preparation of young men and women for lasting marriages. The authors intended to discuss this issue in Awkunanaw through the lens of Genesis 24:48–54. This passage can serve as prototype of a good mediation in marriage, promoting healthy human relationship in Awkunanaw. Contribution: The study offers middle persons in Awkunanaw the opportunity to improve their mediatory roles in marriage practices. Contemporary mediators can emulate Eliezer’s idiosyncrasy to ensure preservation of cultural heritage and guide the younger generation more effectively.